The open-ended city : David Dillon on Texas architecture - Dillon, David, 1941-2010 (University of Texas Press, 2019)
In 1980, David Dillon launched his career as an architectural critic with a provocative article that asked "Why Is Dallas Architecture So Bad?" Over the next quarter century, he offered readers of the Dallas Morning News a vision of how good architecture and planning could improve quality of life, combatting the negative effects of urban sprawl, civic fragmentation, and rapacious real estate development typical in Texas cities. The Open-Ended City gathers more than sixty key articles that helped establish Dillon?s national reputation as a witty and acerbic critic, showing readers why architecture matters and how it can enrich their lives. Kathryn E. Holliday discusses how Dillon connected culture, commerce, history, and public life in ways that few columnists and reporters ever get the opportunity to do. The articles she includes touch on major themes that animated Dillon?s writing: downtown redevelopment, suburban sprawl, arts and culture, historic preservation, and the necessity of aesthetic quality in architecture as a baseline for thriving communities. While the specifics of these articles will resonate with those who care about Dallas, Fort Worth, and other Texas cities, they are also deeply relevant to all architects, urbanists, and citizens who engage in the public life and planning of cities. As a collection, The Open-Ended City persuasively demonstrates how a discerning critic helped to shape a landmark city by shaping the conversation about its architecture.